Fiscal Policy Formulation under the Application Sufficiency Economy Philosophy - เอี่ยมวิจารณ, สุบรรณ (Journal of Research and Development Institute Rajabhat Maha Sarakham University, 2016)
Sufficiency Economy Philosophy was originated by his Majesty the King of Thailand, focusing on enabling Thai people, public sector and private sector to have moderation , reasonableness and self-immunity system including knowledge and morality as based. Fiscal Policy is the important for economic development of Thailand. Fiscal Policy Formulation under globalization must have application of Sufficiency Economy Philosophy for suitable toward balanced growth. This academic paper purposes the approach to fiscal policy formulation under the application of Sufficiency Economy Philosophy as the guidance for policy maker in policy formulation with the aim for growth and sustainability.